Estudo de sólidos de revolução com modelagem matemática - (:unkn) unknown (Universidade Federal do Pampa, 2024)
The work proposes a sequence of activities with Mathematical Modeling, with the aim of approaching the topic of Solids of Revolution so that students can realize that solids are related to their daily lives, based on a task that is to bring the objects to the classroom and make comparisons with already known solids, using the Learning Object that was designed to help visualize and verify results. The classes were planned so that studies take place in a more participatory manner at all stages, from choosing the object to validating the results, considering the stages of mathematical modeling by Almeida (2011).
Study of solids of revolution with mathematical modeling
Keywords: Sólidos de revolução; Modelagem matemática; Objeto de aprendizagem; Solids of revolution; Mathematical modeling; Learning object; CNPQ::CIENCIAS EXATAS E DA TERRA